Workload Automation Using HWA : With Architecture and Deployment Options. - Sabharwal, Navin (Apress L. P., 2022)
Apply best practices for deploying and administering HCL Workload automation (HWA) to meet the automation requirements of the digitally transformed platform. This book will provide detailed architecture and deployment options to achieve this goal. Workload automation focuses on real-time processing, predefined event-driven triggers, and situational dependencies. It offers centralized control of managing multiple tasks, making it possible to schedule enterprise-wide tasks. You'll see how it supports the timely completion of tasks and is beneficial for processes that need to happen at a specific time or need to occur as a result of another event. HWA increases efficiency, reduces the turnaround time for workflows, and reduces errors along with delays in end-to-end processes. You'll review proven ways to deliver batch optimization and modernization requirements, and see how solutions can be aligned with the DevSecOps delivery model. Workload Automation Using HWA presents information on how to use the tool and has numerous use cases and implementation procedures to guide every workload automation deployment requirement. ​ What You'll Learn Automate and integrate your complex workload, workflow, and business processes across automation platforms, ERP systems, and business applications Understand event-driven batch automation Practice alignment of the workload automation solution with the DevSecOps principles Who This Book Is For Solution Architects, Infrastructure Architects, Technical Architects, Enterprise Architects, Workload Automation Tool Administrators or SME's, Schedulers, Application owners, Automation Specialists, Service Delivery Managers.